Dinâmica e controle de um sistema Maglev simplificado - Cabral, Thalles Denner Ferreira [UNESP] (2015)
Several experimental Maglev (magnetic levitation transport) systems all around the world, mainly in Germany and Japan have demonstrated that this mode of transportation can profitably compete with air travel. However, a system such as the German Maglev train (called Transrapid) is inherently unstable. This instability is because the electromagnetic suspension system uses attractive force to levitate the train. Herewith, some levitation control system must be implemented to make safe operation. From a simplified model for the Transrapid experimental system is possible to investigate the instability and to propose some control design. In this work, we propose two control designs for the system. The following techniques are used to design the controllers: Linear Quadratic Regulator (LQR) and State-Dependent Riccati Equation (SDRE). The first project is a linear controller, while the other is non-linear. Simulations shows that the SDRE controller allows the Maglev system to operate with much larger disturbances in the air gap than the LQR controller does